Results and Conclusions of the Project “Complex Model for Risk Assessment and Treatment in Industrial Processes” (Mopori) - Katarina Holla; Maria Simonova; Jan Kandrac; Stanislav Maly; Andrew Collins (Communications - Scientific letters of the University of Zilina, 2015)
This article deals with selected results and conclusions which were achieved in the project APVV 0043-10 MOPORI during more than three years of its solution. The area of major industrial accidents prevention is very specific and concerns all EU member states. At the beginning we will describe the current state and bases of the project together with identification of the problem areas. In the next part we will aim at describing the algorithm created for assessing and managing the risks. Here we implemented suitable qualitative and quantitative methods and we will explain its applicability. Subsequently we will present software means for creating scenarios and assess the currently realised application of the model. This application is an inevitable part for verifying the procedures and schemes created.